Devising Interactive Dissolution Experiment for Pharmacy Students (part I): Use of USP Type II Apparatus for Comparison of Immediate Release and Enteric Coated Tablets in Time Varying pH Conditions - Madni, Asadullah; Kanwal, Rabia; Tariq, Marium; Baloch, Ariba; Shah, Komal; Jabbar, Abdul; Khan, Muhammad Imran; Rehman, Mubashar (PSM Biological Research, 2016)
Laboratory experiments are valuable tool for enhancing student’s understanding of theory and practice of science. This manuscript is first part of series which reports interactive dissolution experiments to enhance student’s perception about how conventional and advanced dosage forms are processed by the human body after oral administration. We used USP type II apparatus for this experiment at paddle speed at 50 rpm and temperature at 37°C. pH variations were simulated using hydrochloric acid (HCL) for acidic pH and sodium hydroxide (NaOH) to neutralize it. Commercially available immediate release (Disprin CV) and enteric coated tablets (Loprin) were used as model pH independent and pH sensitive drug delivery systems, respectively. Results showed that immediate release tablet released all contents at acidic pH in less than one minute. On the other hand, enteric coated tablets remained unaffected at acidic pH during 30 min exposure time. When pH of the medium reached to neutral, enteric coated tablet also started releasing drugs and whole drug was released in about 30 min. This study provided students with visual presentation of how enteric coated and immediate release tablets may differ in pattern of drug release in different regions of gastrointestinal tract. Students participated actively in the laboratory experiment and forecasting expected results.